Hybrid Imaging of Aspergillus fumigatus Pulmonary Infection with Fluorescent, 68Ga-Labelled Siderophores - Pfister, Joachim; Summer, Dominik; Petrik, Milos; Khoylou, Marta; Lichius, Alexander; Kaeopookum, Piriya; Kochinke, Laurin; Orasch, Thomas; Haas, Hubertus; Decristoforo, Clemens (Biomolecules, 2020)
Aspergillus fumigatus (A. fumigatus) is a human pathogen causing severe invasive fungal infections, lacking sensitive and selective diagnostic tools. A. fumigatus secretes the siderophore desferri-triacetylfusarinine C (TAFC) to acquire iron from the human host. TAFC can be labelled with gallium-68 to perform positron emission tomography (PET/CT) scans. Here, we aimed to chemically modify TAFC with fluorescent dyes to combine PET/CT with optical imaging for hybrid imaging applications. Starting from ferric diacetylfusarinine C ([Fe]DAFC), different fluorescent dyes were conjugated (Cy5, SulfoCy5, SulfoCy7, IRDye 800CW, ATTO700) and labelled with gallium-68 for in vitro and in vivo characterisation. Uptake assays, growth assays and live-cell imaging as well as biodistribution, PET/CT and ex vivo optical imaging in an infection model was performed. Novel fluorophore conjugates were recognized by the fungal TAFC transporter MirB and could be utilized as iron source. Fluorescence microscopy showed partial accumulation into hyphae. µPET/CT scans of an invasive pulmonary aspergillosis (IPA) rat model revealed diverse biodistribution patterns for each fluorophore. [68Ga]Ga-DAFC-Cy5/SufloCy7 and -IRDye 800CW lead to a visualization of the infected region of the lung. Optical imaging of ex vivo lungs corresponded to PET images with high contrast of infection versus non-infected areas. Although fluorophores had a decisive influence on targeting and pharmacokinetics, these siderophores have potential as a hybrid imaging compounds combining PET/CT with optical imaging applications.
Keywords: Microscopy, Fluorescence; Protein Binding; Rats, Inbred Lew; Female; fluorescenční mikroskopie; Aspergillus fumigatus; krysa rodu Rattus; zvířata; gallium-68; Invasive Pulmonary Aspergillosis; fluorescenční barviva; fluorescence microscopy; ženské pohlaví; Fluorescent Dyes; Positron Emission Tomography Computed Tomography; kompetitivní vazba; near infrared; Siderophores; vazba proteinů; Hydrogen-Ion Concentration; Binding, Competitive; invazivní plicní aspergilóza; potkani inbrední LEW; Rats; invasive pulmonary aspergillosis; siderophores; PET; radioizotopy galia; siderofory; Animals; Gallium Radioisotopes; koncentrace vodíkových iontů; Disease Models, Animal; PET/CT; modely nemocí na zvířatech